Osteology of the axial and appendicular skeletons of the meagre Argyrosomus regius (Sciaenidae) and early skeletal development at two rearing facilities - Cardeira Da Silva, João (2014)
The meagre (Argyrosomus regius) is a new species for aquaculture diversification, presenting a high economic value and a high growth rate, reaching 1 kg year)1. The occurrence of deformities, which generally appear in cultured larvae at early stages, is problematic for aquaculture since they reduce fish fitness and profitability. Knowledge about the stages of skeletal formation is essential to accurately assess deformities in hatchery produced fish. Here, we describe the osteology of the axial skeleton and unpaired fins of the meagre. Based on this data, the osteological development of meagre larvae reared at the IPIMAR and IRTA-SCR, under different rearing conditions, was compared. Although little literature is available on the osteology of teleosts from the same taxonomic group, the skeletal composition of the meagre is comparable to that of other Sciaenidae. All skeletal structures considered appeared at earlier stages in larvae reared at IPIMAR, which presented a more advanced skeletal development in comparison to larvae of comparable length reared at IRTA-SCR that were submitted to lower temperature and light intensity, and reduced photoperiod regimes.